The Task and the Scope of the Science of Human Action – Part III:: Science and Value - Mises, Ludwig von (MISES: Interdisciplinary Journal of Philosophy, Law and Economics, 2016)
The author examines the purposes and the appropriate method for developing research in the field of the social sciences, discussing the origin of these sciences and covering, with particular attention, the fields of economics and sociology. Elaborating a critical stance against both historicism and empiricism, the author argues in favor of a universal science – praxeology, or the science of human action.